Interleukin-6 Signaling Pathway and Its Role in Kidney Disease: An Update - Su, Hua; Lei, Chun-Tao; Zhang, Chun (Frontiers in Immunology, 2017)
Interleukin-6 (IL-6) is a pleiotropic cytokine that not only regulates the immune and inflammatory response, also affects hematopoiesis, metabolism and organ development. IL-6 can simultaneously elicit distinct or even contradictory physiopathological processes, which is likely discriminated by the cascades of signaling pathway, termed classic and trans-signaling. Besides playing several important physiological roles, deregulated IL-6 has been demonstrated to underlie a number of autoimmune and inflammatory diseases, metabolic abnormalities and malignancies. This review provides an overview of basic concept of IL-6 signaling pathway as well as the interplay between IL-6 and renal resident cells, including podocytes, mesangial cells, endothelial cells and tubular epithelial cells. Additionally, we summarize the roles of IL-6 in several renal diseases, such as IgA nephropathy, lupus nephritis, diabetic nephropathy and acute kidney injury.